THE IMPLICATIONS OF OZEMPIC-INDUCED WEIGHT REDUCTION: A TRANSIENT REMEDY WITH PROLONGED AFTEREFFECTS - Milošević Sopta, Nastasija; Djordjić, Jelena (Archives of Pharmacy, 2023)
Ozempic (semaglutide) is a medication prescribed for type 2 diabetes management. Recent attention has focused on its off-label use for weight reduction, driven by prominent social media endorsements (1,2). Although not being registered for weight loss, this has led to increased demand, supply shortages, and impacts on diabetes treatment. Despite promising weight loss effects, it carries significant risks. We examined Ozempic use in Serbia, with a focus on off-label weight management and insulin resistance. We conducted a cross-sectional study in 30 Serbian pharmacies from February to April 2023. Data on Ozempic prescriptions, indications, and funding sources were collected. A pharmacist survey assessed roles of pharmacists, regulatory measures, and off-label criteria. Most Ozempic prescriptions targeted type 2 diabetes, primarily funded by health insurance, and which required prescriptions or medical reports for commercial purchases. Pharmacists reported rising use for insulin resistance and obesity, prompting stricter oversight. During the study, Ozempic demand for weight management surged, leading some diabetic patients to seek it abroad. Despite media attention, Ozempic and GLP-1 medications lack approval for broader use. Patients outside the specified demographic face increased risk, with limited safety data for lower body weights. It’s crucial to inform patients and healthcare providers about Ozempic’s temporary weight loss effects and potential post-discontinuation weight regain, and potential unforeseen side effects. The widespread off-label use of Ozempic for weight management significantly affects its availability for type 2 diabetes. Promoting a holistic approach to weight management, focusing on lifestyle modifications rather than relying solely on Ozempic, is essential.